SURVEILANS HAMA UTAMA DAN PENGENDALI EKOSISTEM ALAMI ENTOMOPATOGEN DI SENTRA BUDIDAYA JAGUNG KECAMATAN SUMBANG, KABUPATEN BANYUMAS - Nur Kholida Wulansari; Ratna Dwi Hirma Windriyati; Larin Tikafebrianti (UNU Purwokerto, 2022)
Corn is a food crop that replaces rice. The nutrients contained in corn include carbohydrates, protein and some dietary fiber content needed by the body, such as Ca, Mg, K, Na, P, Ca and Fe. In an effort to increase corn production, there are many obstacles, one of which is the presence of pests. The pests that attack corn include the caterpillar pest (Spodoptera sp.). This research was carried out from June to September 2021 at the Corn Crop Cultivation Center, Sumbang District and the Integrated Laboratory of the Nahdlatul Ulama University, Purwokerto. The population of Spodoptera in the Subdistrict of Sumbang is Spodoptera fugiperda. The highest intensity of S. frugiperda attack was 74.6%. The high intensity of the attack is influenced by the age of the plant, the variety, and the cultivation method carried out by the farmer. The high dose of synthetic pesticides used by farmers makes it difficult to find the presence of entomopathogens. The entomopathogen found in the research area was Metharizium rileyi.